Executive Agreements in the US Legal Esoterica - Manoltzas, Filippos (2021)
This dissertation is a call for a return to the American constitutional treaty-making standards, which have been perilously undermined, as important international commitments of the United States are being made by executive agreements instead of treaties. Its central thesis is that the executive branch of the US Federal Government must cast an anchor to its “constitutional moorings” and rely less on executive agreements, which are concluded without senatorial advice and consent. It also contends that it is to the benefit of the President to keep the US Senate involved in foreign policymaking, for only collective deliberation and action on key issues is politically wise and constitutionally allowed.; Master of Arts in Law and Diplomacy, September 2005; Thesis Submitted by Filippos Manoltzas Under the Advisement of Professors MICHAEL GLENNON and LUCIUS CAFLISCH; Tufts University, The Fletcher School of Law and Diplomacy University of Geneva, The Graduate Institute of International Studies